Easily encodable/decodable digital polymers linked by dithiosuccinimide motif - Ding, Kunshan; Zhang, Yajie; Huang, Zhihao; Liu, Baolei; Shi, Qiunan; Hu, Lihua; Zhou, Nianchen; Zhang, Zhengbiao; Zhu, Xiulin (European polymer journal, 2019)
The easily encodable and decodable digital polymer using dithiosuccinimide as sequence building block and sequencing indicator was proposed. [Display omitted] •The easily encodable and decodable digital polymer was realized.•Dithiosuccinimide was used as the sequence building block for facile encoding information.•Dithiosuccinimide was used as the sequencing indicator was proposed for the ease of decoding information. Digital polymers with precise arrangements of units acting as the 0- or 1-bit, have shown bright promise for the data storage media. The easiness of encoding and decoding these polymers is essential when putting them into practical applications. Herein, the concept of utilizing sequence building block and sequencing indicator to generate easily encodable and decodable digital polymers is proposed. With the thiol-maleimide Michael coupling for digital chain growth, the dithiosuccinimide (DTS) motifs generated from the succinimide thioether linkages are used as the sequence building block. The DTS can be equipped with different groups, thus greatly enabling the modular encoding process. Importantly, the tandem mass spectrometry (MS/MS) results unveil the relatively abundant DTS-induced MS signal, which facilitates the decoding process with DTS acting as the sequencing indicator. The synergetic MS/MS induced cleavages of the two CS bonds on DTS are responsible for the relatively abundant MS signal. Finally, the work exemplifies the quantitatively decoding of a digital polymer with DTS as the sequence building block and sequencing indicator. This study demonstrates the concept of sequence building block and sequencing indicator, which advances the digital polymers for practical applications.